Curriculum Reform in Practice: Novice English Teachers’ Adaptation and Challenges under the Merdeka Framework - Miftahul Jannah; Rahma Ibtida Saumi; Novia Fitrian; Tria Angela Kusumaningrum; Zaitun Qamariah (CV. Doki Course and Training, 2025)
This study examined the experiences of novice English teachers in implementing the Merdeka Curriculum in Indonesian public school. Using a qualitative method through case study approach, data were collected from three early-career English teachers through interviews and document analysis. Thematic analysis revealed three key themes: implementation challenges, support systems, and effective teaching techniques. Teachers faced obstacles such as limited technical skills, inadequate facilities, and passive student behavior. However, they adapted by modifying tasks, using multimedia, grouping students flexibly, and using assessments to plan lessons. Support came mainly from digital platforms and peer groups, while formal mentoring was lacking. The study concludes that successful curriculum implementation requires strong institutional support, sufficient infrastructure, and teacher readiness. These insights provide practical guidance for new teachers facing curriculum reform.